Collaborative Care for Psychiatric Disorders in Older Adults: A Systematic Review. (November 2017) - Dham, Pallavi; Colman, Sarah; Saperson, Karen; McAiney, Carrie; Lourenco, Lillian; Kates, Nick; Rajji, Tarek K.
Objective: To evaluate the mode of implementation, clinical outcomes, cost-effectiveness, and the factors influencing uptake and sustainability of collaborative care for psychiatric disorders in older adults. Design: Systematic review. Setting: Primary care, home health care, seniors' residence, medical inpatient and outpatient. Participants: Studies with a mean sample age of 60 years and older. Intervention: Collaborative care for psychiatric disorders. Methods: PubMed, MEDLINE, Embase, and Cochrane databases were searched up until October 2016. Individual randomized controlled trials and cohort, case-control, and health service evaluation studies were selected, and relevant data were extracted for qualitative synthesis. Results: Of the 552 records identified, 53 records (from 29 studies) were included. Very few studies evaluated psychiatric disorders other than depression. The mode of implementation differed based on the setting, with beneficial use of telemedicine. Clinical outcomes for depression were significantly better compared with usual care across settings. In depression, there is some evidence for cost-effectiveness. There is limited evidence for improved dementia care and outcomes using collaborative care. There is a lack of evidence for benefit in disorders other than depression or in settings such as home health care and general acute inpatients. Attitudes and skill of primary care staff, availability of resources, and organizational support are some of the factors influencing uptake and implementation. Conclusions: Collaborative care for depressive disorders is feasible and beneficial among older adults in diverse settings. There is a paucity of studies on collaborative care in conditions other than depression or in settings other than primary care, indicating the need for further evaluation.